Protocolo para identificación de criterios de producción más limpia en la selección de estudios de caso en empresas del sector manufacturero competitivas y altamente contaminantes (2013)
The final results of this project will become a useful management tool to determine current conditions from which it is intended to achieve economic growth, social equity and respect for the environment simultaneously. Starting from those premises the author analyzed successful international models in order to identify the main criteria of the cleaner production model, which has been applied as a preventive environmental strategy, oriented lifecycle product, together with initiatives based on sustainability of natural resources, intended to minimize waste and emissions and maximize product output.